Seasonality and Genotype Diversity of Human Rhinoviruses during an Eight-Year Period in Slovenia - Nataša Berginc; Maja Sočan; Katarina Prosenc Trilar; Miroslav Petrovec (Microorganisms, 2024)
Due to the high socioeconomic burden of rhinoviruses, the development of prevention and treatment strategies is of high importance. Understanding the epidemiological and clinical features of rhinoviruses is essential in order to address these issues. Our study aimed to define the seasonality and molecular epidemiology of rhinoviruses in Slovenia. Over a period of eight years, a total of 20,425 patients from sentinel primary healthcare settings and sentinel hospitals were examined for a panel of respiratory viruses in the national programme for the surveillance of influenza-like illnesses and acute respiratory infections. The patients were from all age groups and had respiratory infections of various severity. Infection with a rhinovirus was confirmed using an RT-rPCR in 1834 patients, and 1480 rhinoviruses were genotyped. The molecular analysis was linked to demographical and meteorological data. We confirmed the year-round circulation of rhinoviruses with clear seasonal cycles, resulting in two seasonal waves with peaks in spring and autumn. High levels of genotype variability and co-circulation were confirmed between and within seasons and were analysed in terms of patient age, the patient source reflecting disease severity, and meteorological factors. Our study provides missing scientific information on the genotype diversity of rhinoviruses in Slovenia. As most previous investigations focused on exclusive segments of the population, such as children or hospitalised patients, and for shorter study periods, our study, with its design, size and length, contributes complementary aspects and new evidence-based knowledge to the regional and global understanding of rhinovirus seasonality and molecular epidemiology.